"Proximalization is Advancement"—Zone 3 Frozen Elephant Trunk vs Zone 2 Frozen Elephant Trunk: A Literature Review. (August 2021) - Choudhury, Rozina Yasmin; Basharat, Kamran; Zahra, Syeda Anum; Tran, Tien; Rimmer, Lara; Harky, Amer; Idhrees, Mohammed; Bashir, Mohamad
Over the decades, the Frozen Elephant Trunk (FET) technique has gained immense popularity allowing simplified treatment of complex aortic pathologies. FET is frequently used to treat aortic conditions involving the distal aortic arch and the proximal descending aorta in a single stage. Surgical preference has recently changed from FET procedures being performed at Zone 3 to Zone 2. There are several advantages of Zone 2 FET over Zone 3 FET including reduction in spinal cord injury, visceral ischemia, neurological and cardiovascular sequelae. In addition, Zone 2 FET is a technically less complicated procedure. Literature on the comparison between Zone 3 and Zone 2 FET is scarce and primarily observational and anecdotal. Therefore, further research is warranted in this paradigm to substantiate current surgical treatment options for complex aortic pathologies. In this review, we explore literature surrounding FET and the reasons for the shift in surgical preference from Zone 3 to Zone 2.